Design of Multi-Wing Deployment Mechanism Based on Multiple Performance Indicators and Topology: Theoretical and Experimental Study - Guangqing Zhai; Jianguo Tao; Hong Xiao; Hongwei Guo; Guang Yang; Runchao Zhao; Chen Yao; Rongqiang Liu (Applied Sciences)
The folding wing deployment mechanisms of aircraft are constrained by weight and space limitations, necessitating fewer actuators, multiple outputs, compact designs, and high efficiency. However, existing folding wing mechanisms often overlook the impact of performance in configuration design. Additionally, they struggle to achieve the synchronous unfolding of multiple wings using a single drive. This paper presents a design methodology for multi-wing deployment mechanisms based on configuration topology and multiple performance indicators. Specifically, seventeen configurations of multi-wing deployment mechanisms are developed based on functional requirements, along with expression methods for performance indicators, including compactness, mechanism stiffness, dynamic sensitivity, motion transmission, and joint transmission efficiency. The optimal configuration for the multi-wing deployment mechanism is identified utilizing the fuzzy comprehensive evaluation. Moreover, the transmission efficiency of multiple configurations is calculated across different scale parameters. Simulation analyses and prototype experiments are conducted to validate the design. The results indicate that the transmission efficiency of the optimized configuration consistently exceeds that of the other configurations. Maximum efficiencies surpass those of the other configurations by 2.4% and 5.7%. Importantly, this study introduces a quantitative expression method for multiple performance indicators at the configuration design stage. This approach enables the integration of various performance metrics with configuration designs. Overall, this research provides a novel approach for the innovative design of multi-wing deployment mechanisms in aircraft. Additionally, considering performance in the selection of mechanism configurations during engineering design offers valuable insights and potential applications.